Предмет: Алгебра,
автор: konstantin1488
помогите пожалуйста
Ответы
Автор ответа:
0
log(2)[5x-3]-log(2)[((x-1)^3)^1/3)]=log(2)[x]+log(2)[2]
log(2)[(5x-3)/(x-1)]=log(2)[2x]
(5x-3)/(x-1)=2x
5x-3=2x(x-1)
2x^2-7x+3=0
(x-3)(2x-1)=0
x=3,1/2
область определения:
(5x-3)/(x-1)>0
x>1; x<3/5
Оба ответа в области определения.
Похожие вопросы
Предмет: Биология,
автор: raimbekkenessarin
Предмет: Информатика,
автор: Marighamm
Предмет: Оʻzbek tili,
автор: Аноним
Предмет: Химия,
автор: Mello97
Предмет: Математика,
автор: nikefootball2012